The Effect of Hand and Power Driven Root Canal - L. Gregor; L. Roubalíková (Czech Dental Chamber, 2006)
The authors compare the cleaning effect of various root canal preparation techniques (hand as well as power driven preparation). Two hand techniques (circumferential filing and balanced force technique) and two power driven techniques (the rotary system Wizard CD Plus, Medin, CR, and oscillating NiTi instruments AET Endo-EZE, Ultradent, USA) were used. The preparation was provided under standard conditions (lubrication with the EDTA gel, rinsing with 2% NaOCl). After the preparation the specimen were split longitudinaly and observed in SEM using the three step scala of the cleanliness of the root canal walls. Part of the specimen was split transversaly and observed macroscopically with magnification 5x. The time of the preparation (circumferential filing and rotary preparation) was comapred using the clear resin blocks. The cleanliness of the root canal walls after the hand preparation techniques was comparable to that after the rotary preparation. The preparation using the oscillating instruments (AET Endo -EZE) showed more smear layer and debris in comparsion to the others methods. In all cases the unprepared areas were found. The preparation with the rotary instruments was less time consuming in compasrion to the circumferential filing.